A method of forming a near net composite gear
Patent Information
- Application Number
- CN202511147013.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-15
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2045-08-15
AI Technical Summary
[0004]鉴于上述的分析,本发明实施例旨在提供一种近全复合材料齿轮,用以解决现有技术中,全金属齿轮重量大、惯性阻力高、运行噪音显著,复合材料齿轮因辐板局部替换导致的减重效果有限等问题中的至少一个
[0020]与现有技术相比,本发明至少可实现如下有益效果之一:
Smart Images

Figure CN120985057B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of gear manufacturing technology, and specifically to a method for forming near-all-composite material gears. Background Technology
[0002] The transmission system is an indispensable part of the normal operation of various large machines. The comprehensive performance of the transmission system directly affects the safety, reliability, and sophistication of large machines. Among the various performance evaluation indicators of the transmission system, power density is always one of the most critical indicators. As an important component of the transmission system, gears can have their power density significantly improved by applying composite materials to the gear structure.
[0003] Traditional gears mostly employ an all-metal structure, resulting in problems such as high weight, high inertial resistance, and significant operating noise. In recent years, resin-based composite gears have become a research hotspot due to their lightweight, corrosion resistance, and self-lubricating properties. In existing technologies, some solutions attempt to replace the gear spokes with resin-based composites, while the gear ring and shaft remain all-metal structures; however, the weight reduction effect is generally limited. If resin-based composites are applied to the gear ring and shaft, their load-bearing capacity and wear resistance are still significantly lower than those of metal materials, restricting their application in high-load scenarios. Summary of the Invention
[0004] In view of the above analysis, the present invention aims to provide a near-all-composite material gear to solve at least one of the problems in the prior art, such as the large weight, high inertial resistance, and significant operating noise of all-metal gears, and the limited weight reduction effect of composite material gears due to partial replacement of spokes.
[0005] On the one hand, this invention proposes a method for forming near-all-composite material gears, comprising the following steps:
[0006] S1. Prepare the composite material gear matrix and reserve a gap for installing the reinforcing column at the tooth root;
[0007] S2. A reinforcing post is provided at the tooth root of the composite gear matrix;
[0008] S3. Assemble the prefabricated metal gear ring around the periphery of the composite gear matrix to form an assembly gap;
[0009] S4. Fill the assembly gap and around the reinforcing column with explosive bonding material;
[0010] S5. An explosive bonding process is used to integrate the metal gear ring edging, reinforcing column, and composite material gear matrix.
[0011] Furthermore, the composite gear matrix is prepared by compression molding of resin-based composite materials.
[0012] Furthermore, the metal gear ring has a thickness of 1 to 5 mm and a surface hardness of HRC58-75; and the assembly gap between it and the composite material gear matrix is controlled within the range of 0.5 to 2 mm.
[0013] Furthermore, the reinforcing columns are 4 to 9 aluminum alloy columns, arranged in 1 to 2 rows along the radial direction of the gear; when arranged in a single row, the number of reinforcing columns is even and the diameter varies in a gradient; when arranged in a double row, the number of reinforcing columns in the first row is even and the diameter varies in a gradient, while the number of reinforcing columns in the second row is odd, the diameter is the same, and the number is less than that in the first row.
[0014] Furthermore, the gradient change is manifested in that the diameter of the reinforcing columns on both sides is 10% to 20% larger than that of the middle one; when arranged in a double row, the diameter of the second row of reinforcing columns is the same as the diameter of the reinforcing columns on both sides of the first row.
[0015] Furthermore, the explosive bonding material is titanium-aluminum alloy powder, with a titanium to aluminum volume ratio of 1:6 to 1:4.
[0016] Furthermore, the explosive bonding process involves covering the outer surface of the metal toothed ring edge with a layer of plastic explosive with a detonation velocity of 2000-3000 m / s, and is carried out in a vacuum environment.
[0017] Furthermore, the explosive bonding process is carried out at a temperature of 200-400℃, a pressure of 200-500MPa, and an interfacial bonding strength of ≥700MPa.
[0018] Furthermore, the material of the metal gear ring edging includes: tempered alloy steel, titanium alloy, or metal-based composite material.
[0019] On the other hand, the present invention proposes a near-all-composite gear prepared according to the above-described method, comprising a resin-based composite gear matrix, a metal gear ring edging, a reinforcing post, and a connecting interface formed by explosive bonding, wherein the interfacial bonding strength between the metal gear ring edging and the composite gear matrix is ≥700MPa.
[0020] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0021] 1) Significant weight reduction and performance balance
[0022] By using resin-based composite materials for the entire composite gear matrix and only adding aluminum alloy reinforcing pillars and metal gear ring edging in the tooth root region, the overall gear weight was successfully reduced by 40%–60% compared to traditional all-metal gears, and by 20%–30% compared to semi-composite gears with only composite spokes. To ensure high load-bearing capacity and wear resistance under the lightweight structure, a high-strength interface connection between the metal gear ring and the resin matrix was achieved through an explosive bonding process (interface strength ≥700MPa), thereby reliably transferring loads and avoiding interface failure. At the same time, the metal gear ring itself provides a wear-resistant surface and local load-bearing capacity, enabling the overall gear to maintain load-bearing capacity and wear resistance comparable to all-metal gears while significantly reducing weight, thus resolving the technical contradiction of incompatibility between lightweighting and comprehensive mechanical properties.
[0023] 2) Significantly enhanced interfacial bonding strength
[0024] Through an explosive bonding process, combined with a titanium-aluminum alloy powder transition layer, a metallurgical-mechanical composite interface is formed between the metal gear ring edge and the composite matrix. The interface shear strength is more than three times that of traditional bonding processes (≥700MPa). This technology completely overcomes the risk of interface delamination caused by the difference in thermal expansion coefficients between composite materials and metals, and significantly improves the durability of gears under alternating loads.
[0025] 3) Innovative stress optimization design
[0026] To address the stress concentration problem at the tooth root of composite gears, a multi-row gradient diameter reinforcing column design (with the diameter on both sides 10%–20% larger than that in the middle) effectively disperses the stress concentration at the tooth root. Combined with the roughened inner surface (Ra≥6.3μm) of the metal gear ring edge and an explosive bonding process, a three-dimensional stress transfer network is formed, improving the gear's fatigue life and overall stability, resulting in better performance under high loads and high-frequency alternating loads.
[0027] 4) The product obtained by the near-all-composite material gear forming method of the present invention has been tested and shown that: while maintaining the same load-bearing capacity as traditional metal gears, the contact fatigue limit increases by 10%, and the bending fatigue limit does not decrease, perfectly balancing the performance requirements of lightweight, high load-bearing capacity and long service life.
[0028] In this invention, the above-described technical solutions can be combined with each other to achieve more preferred combinations. Other features and advantages of this invention will be set forth in the following description, and some advantages may become apparent from the description or be learned by practicing the invention. The objects and other advantages of this invention can be realized and obtained from what is particularly pointed out in the description and drawings. Attached Figure Description
[0029] The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. Throughout the drawings, the same reference numerals denote the same parts.
[0030] Figure 1 This is a schematic diagram of the near-all-composite material gear of the present invention;
[0031] Figure 2 This is a schematic diagram of the reinforcing post at the root of the near-all-composite material gear of the present invention.
[0032] Figure label:
[0033] 1-Metal gear ring edging; 2-Gear root; 3-Composite gear matrix; 4-Explosive bonding material. Detailed Implementation
[0034] The preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings, which constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not intended to limit the scope of the present invention.
[0035] This invention provides a method for forming near-all-composite material gears. This method effectively solves the following industry technical problems through an innovative metal-composite material composite structure design:
[0036] Disadvantages of traditional all-metal gears: Traditional all-metal gears have problems such as large weight, high inertial resistance, and significant operating noise.
[0037] The challenges of existing composite gear technology:
[0038] a) The partial composite material replacement scheme that only replaces the spokes has a limited weight reduction effect (10% to 20%) and cannot fully realize the advantages of lightweighting.
[0039] b) All-composite gears are difficult to put into practical use because key load-bearing components such as gear rings and gear shafts are limited by the performance bottlenecks of composite materials (e.g., insufficient load-bearing capacity, poor wear resistance, low thermal stability, complex interface bonding and manufacturing process).
[0040] The specific technical measures of this invention are as follows:
[0041] 1) Significantly Lightweight Design: The gear matrix is made entirely of resin-based composite material, encompassing the spokes, gear ring body, and gear shaft. Localized metal reinforcement structures, such as aluminum alloy reinforcing columns and alloy steel edging, are only incorporated in critical stress areas like the tooth root and tooth surface. This structure results in a 40%–60% weight reduction compared to traditional all-metal gears, and a further 20%–30% weight reduction compared to semi-composite gears where only the spokes are composite. This design effectively solves the problems of high weight, high inertial resistance, and significant operating noise associated with traditional all-metal gears.
[0042] 2) High-strength interfacial bonding: A high-strength alloy steel sheet with a thickness of 0.5–2 mm is used to wrap the outer surface of the gear ring. Optimized explosive bonding process parameters achieve a high-strength bond (interfacial strength ≥700 MPa) between the metal gear ring edging and the resin-based composite gear matrix. Simultaneously, precise control of the explosive bonding temperature prevents thermal damage to the resin matrix, allowing the gear to combine the lightweight advantages of composite materials with the high load-bearing capacity of metal.
[0043] 3) Tooth root stress optimization: An aluminum alloy reinforcing column structure with a diameter of 3-8mm is installed in the tooth root region, and a gradient diameter design is adopted, that is, the diameter on both sides is 10%-20% larger than that in the middle. This effectively alleviates the problem of stress concentration at the tooth root of composite gears. Utilizing the explosive shock wave, a composite connection of metallurgical bonding and mechanical interlocking between the titanium-aluminum alloy and the resin matrix is formed at the interface, giving the gear both lightweight and high load-bearing capacity, significantly improving fatigue life, making it suitable for high-load conditions, and greatly expanding the application range of gears.
[0044] On one hand, this invention discloses a method for forming near-all-composite material gears, comprising the following steps:
[0045] S1. Prepare the composite material gear matrix and reserve a gap for installing the reinforcing column at the tooth root;
[0046] S2. A reinforcing post is provided at the tooth root of the composite gear matrix;
[0047] S3. Assemble the prefabricated metal gear ring around the periphery of the composite gear matrix to form an assembly gap;
[0048] S4. Fill the assembly gap and around the reinforcing column with explosive bonding material;
[0049] S5. An explosive bonding process is used to integrate the metal gear ring edging, reinforcing column, and composite material gear matrix.
[0050] Furthermore, in S1, this invention, through innovative mold design, high-performance prepreg preparation, and optimized molding process, ensures that the gear matrix possesses excellent dimensional accuracy and mechanical properties, providing a solid foundation for subsequent explosive bonding processes and the overall performance of the gear. The specific steps for preparing the composite gear matrix are as follows:
[0051] S001. Mold Preparation: Based on the design drawings of the gear base, considering the impact of thermal expansion of the metal mold on the dimensional accuracy of the product at the forming temperature (200-250℃), the mold is appropriately reduced in size, such as reducing the overall mold cavity size by 0.15%–0.20%; preferably 0.18%. This step, through mold reduction compensation and subsequent optimized molding parameters, solves the problem of insufficient dimensional accuracy of traditional composite gears due to thermal expansion, ensuring that the base can meet the high-precision assembly requirements of subsequent metal gear ring edging.
[0052] For example, the "mold shrinkage compensation" includes:
[0053] Step 1. Measure the coefficient of linear expansion α of the mold steel at three points: 200℃, 220℃, and 250℃.
[0054] Step 2. Calculate the total expansion at the corresponding temperature ΔL = α·L·ΔT; where ΔT = T 成型 -T 室温 L is the reference dimension of the mold cavity, T 成型 The highest process temperature is set at 250℃.
[0055] Step 3. Determine the overall reduction ratio (0.15%–0.20%) of the mold cavity size based on ΔL and the reference dimension L. This ratio is derived from a comprehensive evaluation of the quantitative analysis of thermal expansion and product accuracy requirements.
[0056] The "optimized molding parameters" include: mold preheating to 200±5℃, curing pressure 5-20MPa, holding time 8-12h, cooling rate 3-5℃ / min, and demolding temperature ≤60℃; the above combination enables the outer diameter tolerance of the substrate to be controlled within ±0.02mm, meeting the high-precision assembly requirements of subsequent metal gear ring edging.
[0057] S002. Prepreg Preparation: High-quality prepreg is prepared by combining EC240A bismaleimide resin and CF700S carbon fiber, and by precisely controlling key process parameters (such as film-forming temperature, coating temperature, and lamination temperature). Specifically, this includes:
[0058] 1) Adhesive film preparation: Precisely control the baking temperature to 101-140℃ and the scraping temperature to 97-128℃ to ensure the adhesive film surface density is 32±2g / m³. 2 ;
[0059] 2) Pre-impregnation process: Install the CCF700S fiber shaft on the yarn rack of the pre-impregnation machine, set the composite temperature to 100-122℃, the roller gap to 0.3±0.05mm, and the initial linear speed to 2~4m / min (dynamically adjusted according to the pre-impregnation effect);
[0060] 3) Tension control: A double-layer adhesive film process is adopted, and the tension of the upper adhesive film (clockwise) and the lower adhesive film (counterclockwise) are both controlled at 100-120N (30%-40%), and the winding tension is 35%-45%.
[0061] 4) Finished product control: The final surface density is 200±5g / m³. 2 The prepreg has a fiber areal density precisely controlled at 135±4 g / m². 2 .
[0062] This high-performance resin-fiber combination and precisely controlled prepreg process, combined with subsequent molding, significantly improves the flexural strength of the composite material compared to conventional nylon composite materials, providing excellent mechanical performance for key load-bearing components such as tooth roots.
[0063] S003, Compression molding:
[0064] The prepared prepreg is placed in a mold preheated to 200±5℃, and an appropriate curing pressure (5-20MPa) is applied through an autoclave. The mixture is then held at 200–250℃ (e.g., 200℃, 210℃, 220℃, 230℃, 240℃, 250℃) for 8–12 hours (e.g., 8h, 9h, 10h, 11h, 12h). This prepreg lamination process ensures an internal bonding strength of over 100MPa within the composite gear matrix. The mixture is then cooled at a rate of 3–5℃ / min (e.g., 3℃ / min, 3.5℃ / min, 4℃ / min, 4.5℃ / min, 5℃ / min) to a demolding temperature ≤60℃ (e.g., 60℃, 50℃, 40℃, 30℃) to obtain the composite gear matrix. The outer diameter tolerance of the base material is controlled within ±0.02mm (e.g., ±0.01mm, ±0.015mm, ±0.02mm) to meet the high-precision assembly requirements of subsequent metal gear ring edging.
[0065] This optimized low-temperature curing process controls the molding temperature at 200–250℃, avoiding thermal damage to the resin matrix caused by traditional high-temperature curing above 180℃, thus ensuring the structural integrity and mechanical properties of the gear matrix.
[0066] Through the above steps—using precise mold compensation, high-performance prepreg preparation, and optimized molding process—composite gear matrices with accurate dimensions and excellent performance can be efficiently produced, providing a solid foundation for subsequent explosive bonding processes and the overall performance of the gears, successfully overcoming the technical bottleneck of composite gears in high-load applications.
[0067] Furthermore, the composite gear matrix of the present invention is preferably prepared using a resin-based composite material through a compression molding process. This material itself possesses inherent properties such as lightweight, excellent fatigue resistance, and superior vibration and noise control, making it particularly suitable for the explosive bonding process of the present invention. Simultaneously, the compression molding process unique to the present invention (including precise die shrinkage compensation, optimized prepreg formulation, and low-temperature curing process) further enhances the material's low thermal conductivity and high toughness, enabling it to achieve effective metallurgical bonding with the metal gear ring under the action of an explosive shock wave, while preventing thermal damage and ensuring the structural integrity and performance stability of the composite gear matrix. Specifically, using a thermosetting resin matrix such as epoxy resin, the preparation process of the present invention can maintain structural stability within a temperature range of 200-300°C without thermal degradation.
[0068] However, all-composite gears have limitations in terms of tooth surface strength and wear resistance, which restricts their application in high-load environments. This invention significantly improves the load-bearing capacity and wear resistance of gears by using a metal-composite composite structure design and assembling a metal gear ring edge with special surface strengthening treatment around the outer periphery of the composite gear matrix.
[0069] The special surface strengthening treatments include, but are not limited to: carburizing and quenching, nitriding, surface coating (such as chromium plating, nickel plating), laser surface strengthening, etc. These treatments can significantly improve the surface hardness, wear resistance and fatigue life of metal gear rings.
[0070] Specifically, the metal toothed ring edge used in this invention has the following preferred features:
[0071] (1) The thickness is controlled within the range of 1 to 5 mm, such as 1 mm, 2 mm, 3 mm, 4 mm, and 5 mm. Such a thickness design not only ensures sufficient load-bearing capacity, but also helps to maintain the lightweight characteristics of the gear, achieving the best balance between performance and weight.
[0072] (2) The surface hardness is HRC58-75, preferably made of tempered alloy steel, titanium alloy or metal matrix composite material to obtain the best balance between wear resistance and mechanical strength.
[0073] (3) After specific surface roughness treatment, the outer surface roughness Ra is greater than 1.6μm to enhance the bonding strength, and the inner surface roughness Ra is less than 6.4μm to ensure assembly accuracy.
[0074] For example, when using high-strength heat-resistant gear steel plates of quenched and tempered alloy steel (such as grade 18Cr2Ni4WA or AISI4340), the metal gear ring edging can be prepared by the following steps:
[0075] a) Preforming process: High-strength heat-resistant gear steel plates are preformed into a basic shape of a gear ring with multiple grooves using a hydraulic press. The grooves are precisely matched with the tooth profile of the composite material gear matrix.
[0076] b) Heat treatment and cold working:
[0077] Heat treatment: The preformed gear ring is heated to 850-950℃ (e.g., 850℃, 870℃, 890℃, 900℃, 920℃, 950℃) for austenitization treatment, held at the temperature for 1-2 hours (e.g., 1h, 1.5h, 2h) and then oil quenched.
[0078] Cold working: Tempering treatment is carried out in the temperature range of 200-300℃ (e.g., 200℃, 220℃, 240℃, 260℃, 280℃, 290℃, 300℃) for 2-3 hours (e.g., 2 hours, 2.2 hours, 2.5 hours, 2.8 hours, 3 hours).
[0079] Finishing: Precision machining ensures that the tooth profile accuracy reaches IT7 level.
[0080] c) Surface strengthening treatment:
[0081] Carburizing treatment: Gas carburizing is carried out at 920-950℃ (e.g., 920℃, 930℃, 940℃, 945℃, 950℃), with the carbon potential controlled at 1.0% to 1.2% (e.g., 1.0%, 1.05%, 1.1%, 1.15%, 1.2%), and the carburized layer depth is 0.5 to 1.0 mm (e.g., 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 1.0 mm).
[0082] Shot peening: Use steel shot with a diameter of 0.3-0.6 mm (e.g., 0.3 mm, 0.35 mm, 0.4 mm, 0.5 mm, 0.6 mm) and a shot peening intensity of 0.3-0.5 mmA (e.g., 0.3 mmA, 0.35 mmA, 0.4 mmA, 0.45 mmA, 0.5 mmA).
[0083] Final heat treatment: Low-temperature tempering at 160-180℃ (e.g., 160℃, 165℃, 170℃, 175℃, 180℃) for 2-3 hours (e.g., 2 hours, 2.2 hours, 2.5 hours, 2.8 hours, 3 hours) to achieve a surface hardness of HRC58-75.
[0084] d) Surface quality control: Ensure that the outer surface roughness Ra is greater than 1.6 μm (e.g., 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm, 2.1 μm) to enhance bonding strength; and the inner surface roughness Ra is less than 6.4 μm (e.g., 0.8 μm, 1.6 μm, 2.4 μm, 3.2 μm, 4.0 μm) to ensure assembly accuracy.
[0085] e) Cleaning treatment: Ultrasonic cleaning is used to remove surface impurities, followed by degreasing with acetone solution, and then drying to obtain the finished metal gear ring edge.
[0086] This invention, through the aforementioned precise machining, ensures that the metal gear ring edging forms a geometric shape that perfectly matches the tooth profile of the composite gear matrix. This precise fit design ensures that a uniform, explosive bonding-specific gap is formed between the two after assembly. This gap provides ideal spatial conditions for subsequent filling of explosive bonding material and is a key structural feature to guarantee the quality of the explosive bonding process.
[0087] Furthermore, in S1, a gap is reserved at the tooth root for installing a reinforcing column.
[0088] This invention optimizes the structure of key components such as the tooth root during the manufacturing process of composite gear matrices. Because discontinuous fiber arrangement inevitably occurs during the weaving of fiber reinforcement materials at the tooth root, localized microstructural defect areas are formed. These areas are prone to becoming stress concentration points under load. To overcome this technical bottleneck, this invention establishes an innovative design scheme that reserves a gap for the installation of reinforcing columns at the tooth root.
[0089] Furthermore, in S2, a reinforcing post is provided at the tooth root of the composite material gear matrix to alleviate stress concentration and enhance the overall structural strength and durability of the gear.
[0090] For example, 4 to 9 (e.g., 4, 5, 6, 7, 8, or 9) reinforcing columns are made of aluminum alloy, with the axis of each reinforcing column parallel to the gear axis; the reinforcing columns are arranged in 1 to 2 rows along the radial direction of the gear (see Appendix). Figure 2 The diameter of the gear is ≥1mm (e.g., 1mm, 1.5mm, 2mm, 2.5mm, 3mm). The specific dimensions are determined according to the gear outer diameter, tooth root transition zone curvature and tooth groove angle parameters, and in accordance with conventional strength design principles.
[0091] For a single-row arrangement, the number of reinforcing posts is even, and their diameters gradually decrease from both sides of the tooth root towards the center (R1 > R2), forming a gradient change. Here, R1 represents the maximum radius of the reinforcing posts at both ends of the tooth root, and R2 represents the minimum radius of the central reinforcing post at the tooth root. In a double-row arrangement, the number of reinforcing posts in the first row is also even, and their diameters gradually decrease from both sides of the gear towards the center, forming a gradient change; the number of reinforcing posts in the second row is odd, with the same diameter, and the number is less than that of the first row.
[0092] Specifically, the gradient change is manifested in the fact that the diameter of the reinforcing pillars on both sides is 10% to 20% larger than the diameter of the middle reinforcing pillar. This design helps to distribute stress more evenly, reduce stress concentration, and thus improve the gear's load-bearing capacity and fatigue life. When arranged in a double row, the diameter of the second row of reinforcing pillars is the same as the diameter of the reinforcing pillars on both sides of the first row (both are R1), which helps to maintain the overall balance and symmetry of the gear and further optimizes the gear's performance.
[0093] Furthermore, the reinforcing posts are made of aluminum alloy, a material that exhibits unique advantages during the explosive bonding process. The coefficient of thermal expansion of aluminum alloy lies between that of the resin matrix and the metal gear ring, effectively mitigating the differences in thermal expansion between the different materials and reducing interfacial stress. During explosive bonding, the low melting point and good plasticity of aluminum alloy allow it to achieve effective bonding with the resin matrix and metal gear ring at relatively low temperatures, avoiding thermal damage to the resin material while ensuring connection strength. Through a special diameter gradient arrangement, these reinforcing posts also optimize stress distribution, significantly improving the stability and reliability of the gears during high-speed operation.
[0094] Furthermore, in S3, the assembly gap formed between the metal gear ring edging and the periphery of the composite gear matrix is preferably controlled within the range of 0.5-2mm (e.g., 0.5mm, 1mm, 1.2mm, 1.5mm, 2mm). This gap range aims to optimize the filling effect of explosive bonding materials such as titanium-aluminum alloy powder and ensure a stable metallurgical bond between the metal gear ring edging and the composite gear matrix. If the gap exceeds 2mm, the explosive bonding material may not be fully filled, affecting the bond strength; if the gap is less than 0.5mm, it may restrict the plastic flow of the material, affecting the continuity and uniformity of the bonding layer, and may even lead to local overheating damage to the resin matrix. Therefore, maintaining an assembly gap of 0.5-2mm is crucial for achieving the best bonding effect.
[0095] Furthermore, in S4, the explosive bonding material is a titanium-aluminum alloy powder treated with a binder, wherein the volume ratio of titanium to aluminum is controlled between 1:6 and 1:4 (e.g., 1:6, 1:5.5, 1:5, 1:4.5, 1:4). The binder is a conventional explosive bonding agent, such as paraffin wax, PVA, or EVA, and is used at 0.5%–2% of the total mass of the titanium-aluminum composite powder (e.g., 0.5%, 0.8%, 1.0%, 1.5%, 2.0%), which allows the powder to be formed and maintain the required shape of the explosive bonding layer.
[0096] This invention addresses the challenge of explosive bonding between resin-based composite materials and metals. It innovatively employs binder-treated titanium-aluminum alloy powder as the explosive bonding material, successfully achieving a high-strength bond between the resin-based composite material and the metal. This innovation overcomes the limitation of traditional explosive bonding technology, which is only applicable to metal / metal bonding. Specifically, the innovation of this invention lies in:
[0097] (1) The aluminum component in titanium-aluminum alloy powder has good plastic deformation ability and low melting point, which helps to promote material flow during the explosion impact process, thereby strengthening the interfacial bonding.
[0098] (2) By adding an appropriate amount of titanium, it is helpful to form titanium-aluminum intermetallic compounds (such as TiAl3) at the bonding interface, which significantly enhances the strength of the bonding interface.
[0099] (3) The coefficient of thermal expansion of titanium-aluminum alloy is between that of resin matrix and metal gear ring, which helps to coordinate the thermal expansion differences of different materials, reduce interfacial stress, and improve the long-term stability of the bonding interface.
[0100] (4) The volume ratio of titanium to aluminum is controlled between 1:6 and 1:4 to ensure that the explosion reaction temperature is maintained within the tolerance range of the resin matrix (200-300℃), avoid thermal damage to the resin material, and achieve a reliable connection between the metal and the composite material.
[0101] Experimental results show that, under this ratio, the strength of the explosive bonding interface can reach over 700 MPa, fully demonstrating the effectiveness and reliability of the method of the present invention.
[0102] Furthermore, in S5, the specific steps of the explosive bonding process are as follows:
[0103] S01. Workpiece Assembly: The pre-assembled metal gear ring edging and composite gear matrix assembly are placed in a vacuum heat treatment furnace, and a split-type constraint mold (made of H13 hot work die steel) is installed on the outer periphery of the metal gear ring edging. The mold cavity and the outer contour of the metal gear ring edging are in transition fit to ensure accurate radial positioning during the explosion process; the upper and lower end faces of the assembly remain open to allow free axial deformation.
[0104] S02. Set heat treatment parameters: Set the temperature inside the heat treatment furnace to 200-300℃ (e.g., 200℃, 220℃, 230℃, 240℃, 250℃, 260℃, 280℃) and the pressure to 200-300MPa (e.g., 200MPa, 220MPa, 230MPa, 240MPa, 250MPa, 260MPa, 280MPa, 300MPa) to ensure that the furnace environment meets the requirements of the explosive bonding process.
[0105] S03. Explosive Bonding: Under set temperature and pressure conditions, an explosive reaction is initiated in the titanium-aluminum alloy powder bonding layer located between the metal gear ring edging and the composite gear matrix. The shock wave generated by the explosion causes the titanium-aluminum alloy powder to fully react and bond within the assembly gaps and around the reinforcing pillars.
[0106] S04. Complete the integrated connection: Through the explosive bonding process, the metal gear ring edge, the reinforcing column and the composite material gear matrix are integrated to form a near-all-composite material gear blank.
[0107] S05. Pressure holding and curing: Hold pressure for 6 to 8 hours (e.g., 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours) to ensure that the interface bonding strength reaches or exceeds 700MPa and complete the curing process of the gear blank.
[0108] S06. Finishing: The upper and lower end faces of the near-composite gear blank are finished to obtain near-composite gears with accurate dimensions and surface finish.
[0109] Through the above steps, the explosive bonding process is completed, resulting in a near-all-composite gear with a high-strength bonding interface.
[0110] On the other hand, the present invention discloses a near-all-composite gear prepared according to the above method, comprising a resin-based composite gear matrix, a metal gear ring edging, a reinforcing post, and a connecting interface formed by explosive bonding, wherein the interfacial bonding strength between the metal gear ring edging and the composite gear matrix is ≥700MPa.
[0111] Specifically, the gear matrix, composed of resin-based composite material, serves as the core load-bearing structure. A high-strength metal gear ring tightly wraps around the outer periphery of the gear matrix, forming a wear-resistant working tooth surface. Several reinforcing pillars are evenly distributed within the composite matrix in the tooth root region, with their outer end faces directly contacting the inner surface of the metal gear ring wrapping. Through an explosive bonding process, a high-strength interfacial bonding layer (strength ≥700MPa) is formed between the metal gear ring wrapping and the composite matrix. This bonding layer also extends to the area surrounding the reinforcing pillars, achieving a metallurgical bond between the three components. In this structure, the metal gear ring wrapping provides a wear-resistant tooth surface, the composite matrix achieves lightweighting, and the reinforcing pillars specifically strengthen the tooth root region. The synergistic effect of these three components ensures the overall strength of the gear, optimizes stress distribution, and significantly improves the gear's load-bearing capacity and service life.
[0112] In summary, this invention, through innovative metal-composite material composite structure design and a unique explosive bonding process, successfully achieves a balance between significant weight reduction (40%–60% weight reduction) and performance (interfacial bonding strength ≥700MPa) in gears. It also greatly enhances interfacial bonding strength and optimizes stress distribution. These advantages enable the gears to exhibit superior load-bearing capacity, durability, and stability under complex working conditions such as high loads and high-frequency alternating loads. This effectively solves many problems in traditional gear technology, bringing a major breakthrough to the gear manufacturing field and possessing broad application prospects and significant economic benefits.
[0113] Laboratory tests have verified that the near-all-composite material gear of this invention exhibits excellent performance indicators under standard working conditions: its load-bearing capacity reaches the level of all-metal gears of the same class; its bending fatigue limit is not reduced, and its contact fatigue limit is increased by 10% compared to all-metal gears (based on ISO 6336 standard gear strength test); in terms of wear resistance, after 1×10 6 After several cycles of testing, the tooth surface wear was only 0.02–0.05 mm (using the ISO / TR 15144-1 standard test method); the interfacial bond strength, measured by tensile shear test (according to ASTM D1002 tensile shear test), was ≥700 MPa. These test data fully demonstrate that the present invention achieves significant lightweight advantages while maintaining the load-bearing characteristics of metal gears.
[0114] The present invention will be described in more detail below through specific embodiments. These embodiments are merely descriptions of the best implementation of the invention and do not limit the scope of the invention in any way.
[0115] Example of composite gear matrix preparation
[0116] Preparation Example 1
[0117] A composite gear matrix with a tooth tip circle diameter of 100 mm was prepared.
[0118] The mold is pre-shrinked by 0.18% based on the coefficient of linear expansion at a curing temperature of 220℃. The prepreg uses EC240A bismaleimide resin and CF700S carbon fiber (30% by volume), with a film surface density of 32 g / m³. 2 Prepreg surface density 200g / m³ 2 During molding, the mold is preheated to 220℃, the curing pressure is 10MPa, the pressure is held for 9 hours, and the demolding temperature is 120℃. The finished product has a tooth tip circle diameter of 100mm (±0.02mm), a flexural strength ≥1.8GPa, and an interlaminar shear strength ≥100MPa.
[0119] Preparation Example 2
[0120] The only difference from Preparation Example 1 is that the carbon fiber volume fraction is 20%, the mold is preheated to 210℃ (Tg+10℃), the curing pressure is 5MPa, and the pressure is held for 8h; the tooth tip circle diameter is 97mm, and the bending strength is ≥1.6GPa.
[0121] Preparation Example 3
[0122] The only difference from Preparation Example 1 is that the carbon fiber volume fraction is 40%, the mold is preheated to 230℃ (Tg+30℃), the curing pressure is 20MPa, and the pressure is held for 10h; the tooth tip circle diameter is 103mm, and the bending strength is ≥2.0GPa.
[0123] Example of metal gear ring edge preparation
[0124] Preparation Example A
[0125] a) Select a 3mm thick 30CrNiMo8 steel plate and preform it into a gear ring with an outer diameter of 110mm under a pressure of 350MPa.
[0126] b) Heat the gear ring to 900℃ and hold for 90 minutes, then oil quench it, and then temper it at 250℃ for 150 minutes. Finally, finish-machine the internal gears to IT7 precision.
[0127] c) Carburize in gas at 930℃ for 60 minutes, then shot peening with 0.4mm steel shot, and finally temper at 170℃ for 120 minutes to achieve a surface hardness of HRC 72.
[0128] d) The outer surface is precision machined to a roughness of Ra 1.8 μm, and the inner surface is sandblasted to Ra 4 μm.
[0129] e) After ultrasonic cleaning and acetone degreasing, and drying, a metal toothed ring edge with a thickness of 3mm and an assembly gap of 1mm is obtained.
[0130] Preparation Example B
[0131] The only difference from preparation example A is that the steel plate thickness is changed to 1 mm, the tempering temperature is changed to 200℃, the carburizing time is shortened to 45 min, the final surface hardness is reduced to HRC 70, the finished product thickness is 1 mm, and the assembly gap is 2 mm.
[0132] Preparation Example C
[0133] The only difference from preparation example A is that the steel plate thickness is changed to 2mm, the tempering temperature is increased to 270℃, the carburizing time is extended to 75min, the final surface hardness is increased to HRC 73, the finished product thickness is 2mm, and the assembly gap is 0.5mm.
[0134] Forming method examples
[0135] Example 1
[0136] A method for forming a near-all-composite material gear includes the following steps:
[0137] S1. Prepare the composite gear matrix (Preparation Example 1) and reserve the installation gap for the reinforcing column.
[0138] The composite gear matrix is made of an all-resin-based composite material, which includes carbon fiber and epoxy resin, with carbon fiber accounting for 30% by volume. During the compression molding process, the mold is preheated to 20°C above the glass transition temperature of the resin, a curing pressure of 10 MPa is applied, and the pressure is held for 9 hours to obtain a composite gear matrix with a tooth tip circle diameter of 100 mm.
[0139] S2. A reinforcing post is installed at the tooth root of the composite material gear matrix.
[0140] To address the issues of insufficient angle at the tooth root to allow for the weaving of composite materials and stress concentration, four 7055 cast and forged aluminum alloy pillars are inserted as reinforcing pillars at each tooth root. The insertion depth of the 7055 cast and forged aluminum alloy pillars is consistent with the tooth profile height, and they are closely arranged with the gaps filled with resin. The 7055 cast and forged aluminum alloy pillars are made of high-strength steel.
[0141] S3. Assemble the prefabricated metal gear ring (preparation example A) onto the outer periphery of the composite gear matrix to form an assembly gap.
[0142] High-strength alloy steel plates are selected, and their surface hardness is increased to HRC 58-75 through heat treatment and carburizing. These alloy steel plates are then machined into metal gear rings. The metal gear rings are ring-shaped with grooves that match the tooth profile of the composite gear matrix. Using specialized tooling, the metal gear rings are assembled to the tooth grooves of the composite gear matrix, with their centers aligned. A 1mm gap is provided for explosive bonding. The thickness of the metal gear ring is 3mm. The inner surface of the metal gear ring is sandblasted to a roughness Ra of 4.0μm.
[0143] S4. Fill the assembly gaps and around the reinforcing columns with titanium-aluminum alloy powder, wherein the volume ratio of titanium to aluminum is 1:5, and 1wt% PVB binder is added for spray granulation. After drying at 60℃ for 2 hours, it can be filled.
[0144] S5. An explosive bonding process is used to integrate the metal gear ring edging, reinforcing post, and composite material gear matrix into a single unit. The specific steps are as follows:
[0145] S01. Workpiece assembly: Place the pre-assembled metal gear ring edging and composite material gear matrix assembly into a vacuum heat treatment furnace.
[0146] S02. Set heat treatment parameters: Set the temperature inside the heat treatment furnace to 250℃ and the pressure to 250MPa to ensure that the furnace environment meets the requirements of the explosive bonding process.
[0147] S03. Explosive Bonding: Under set temperature and pressure conditions, an explosive reaction is initiated in the titanium-aluminum alloy powder bonding layer located between the metal gear ring edging and the composite gear matrix. The shock wave generated by the explosion causes the titanium-aluminum alloy powder to fully react and achieve metallurgical bonding in the assembly gaps and around the reinforcing columns.
[0148] S04. Complete the integrated connection: Through the explosive bonding process, the metal gear ring edge, the reinforcing column and the composite material gear matrix are integrated to form a near-all-composite material gear blank.
[0149] S05, Pressure Holding and Curing: Hold pressure for 7 hours to ensure that the interface bonding strength reaches or exceeds 700MPa, and complete the curing process of the gear blank.
[0150] S06. Finishing: Perform tooth profile finishing (CNC grinding) on the gears after explosive bonding to eliminate explosive deformation and obtain near-full composite material gears.
[0151] Example 2
[0152] A method for forming near-all-composite material gears differs from Example 1 only in that:
[0153] In S1, the composite gear matrix (preparation example 2) has the following characteristics: the mold preheating temperature is 10°C above the glass transition temperature of the resin, the carbon fiber volume fraction is 20%, the curing pressure is 5MPa, the holding time is 8 hours, and the tooth tip circle diameter of the composite gear matrix is 97mm.
[0154] In S2, there are 3 7055 cast and forged aluminum alloy columns inserted.
[0155] In S3, the thickness of the metal gear ring edging (preparation example B) is 1 mm;
[0156] In S4, the special gap for explosive bonding is 2mm;
[0157] In S5, the explosive bonding material is titanium-aluminum alloy powder (Ti:Al=1:5) + 1wt% PVA binder.
[0158] Example 3
[0159] A method for forming near-all-composite material gears differs from Example 1 only in that:
[0160] In S1, the composite gear matrix (preparation example 3) has the following characteristics: the mold preheating temperature is 30°C above the glass transition temperature of the resin, the carbon fiber volume fraction is 40%, the curing pressure is 20 MPa, the holding time is 10 hours, and the tooth tip circle diameter of the composite gear matrix is 103 mm.
[0161] In S2, the number of spray-formed aluminum alloy columns inserted is 5;
[0162] In S3, the thickness of the metal gear ring edging (preparation example C) is 2 mm;
[0163] In S4, the special gap for explosive bonding is 0.5mm.
[0164] In S5, the explosive bonding material is titanium-aluminum alloy powder (Ti:Al=1:4) + 1.5wt% EVA binder.
[0165] Example 4
[0166] Based on the substrate of Example 1 and the metal gear ring of Example A prepared in Example 1, the following parameters were adjusted:
[0167] S2, Reinforcing Columns: Three spray-formed aluminum alloy columns are inserted into each tooth root;
[0168] S5. Explosive bonding material: titanium-aluminum alloy powder (Ti:Al=1:6) + 2wt% paraffin binder.
[0169] Example 5
[0170] Based on the substrate of Example 1 and the metal gear ring of Example A prepared in Example 1, the following parameters were adjusted:
[0171] S4, Explosive bonding gap: 2mm;
[0172] S5, titanium-aluminum alloy ratio: Ti:Al=1:4, binder is 1wt% PVB.
[0173] Comparative Example 1
[0174] A type of all-metal gear:
[0175] The gears are manufactured using traditional all-metal materials and processes. The gear material is high-strength alloy steel, produced through conventional forging and machining. The gear's tip circle diameter is 100mm. Composite materials and explosive bonding processes are not involved.
[0176] Comparative Example 2
[0177] Compared to Comparative Example 1, only the gear spokes were replaced with traditional composite materials, while the gear ring and gear shaft still used a metal structure.
[0178] Comparative Example 3
[0179] Near-all-composite gears prepared using traditional bonding processes:
[0180] The composite gear matrix is prepared using the same all-resin-based composite material as in Example 1. No tooth root reinforcing pillars are provided. The metal gear ring is assembled to the periphery of the composite gear matrix using a conventional adhesive bonding process, without involving explosive bonding. The metal gear ring has a thickness of 3 mm and a tip circle diameter of 100 mm.
[0181] Comparative Example 4
[0182] All-composite gears without reinforcing pillars:
[0183] The composite gear matrix is prepared using the same all-resin-based composite material as in Example 1, with a carbon fiber volume fraction of 30%. No tooth root reinforcing posts are provided. The metal gear ring is assembled to the periphery of the composite gear matrix using an explosive bonding process. The explosive bonding clearance is 1 mm, and the explosive bonding material is titanium-aluminum alloy powder (Ti:Al = 1:5) + 1.5 wt% EVA binder. The metal gear ring thickness is 3 mm, and the addendum circle diameter is 100 mm.
[0184] Result characterization
[0185] The test results of Examples 1-5 and Comparative Examples 1-4 are shown in Table 1:
[0186] Table 1
[0187]
[0188] As shown in Table 1, the near-all-composite material gear forming method of the present invention has significant advantages in key performance indicators. Regarding interfacial bonding strength, Examples 1-5 achieve 710–738 MPa, significantly higher than the 420–710 MPa of Comparative Examples 1-4. In terms of gear weight, Examples 1-5 weigh 1.1 kg, far lighter than the 2.5 kg of Comparative Example 1, achieving weight reduction. Regarding tooth surface hardness, the 73 HRC of Examples 1-5 is significantly higher than the 60 HRC of Comparative Examples 2-4. This indicates that the present invention significantly reduces gear weight and improves tooth root fatigue life while improving the overall mechanical properties of the gear, demonstrating good application prospects and economic benefits.
[0189] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for forming near-all-composite material gears, characterized in that, Includes the following steps: S1. Prepare a resin-based composite gear matrix (3) and reserve a gap for installing a reinforcing column at the tooth root (2); S2. A reinforcing post is provided at the tooth root (2) of the composite material gear matrix (3); S3. Assemble the prefabricated metal gear ring edge (1) onto the periphery of the composite material gear matrix (3) to form an assembly gap; S4. Fill the assembly gap and around the reinforcing column with explosive bonding material (4); S5. The metal gear ring edge (1), the reinforcing column and the composite material gear matrix (3) are integrated by using an explosive bonding process.
2. The forming method according to claim 1, characterized in that: The composite gear matrix (3) is prepared by compression molding of resin-based composite material.
3. The forming method according to claim 1, characterized in that: The metal gear ring edging (1) has a thickness of 1 to 5 mm and a surface hardness of HRC58-75; and the assembly gap between it and the composite material gear matrix (3) is controlled within the range of 0.5 to 2 mm.
4. The forming method according to claim 1, characterized in that: The reinforcing columns consist of 4 to 9 aluminum alloy columns, arranged in 1 to 2 rows along the radial direction of the gear. When arranged in a single row, the number of reinforcing columns is even and their diameters vary in a gradient. When arranged in a double row, the number of reinforcing columns in the first row is even and their diameters vary in a gradient, while the number of reinforcing columns in the second row is odd, with the same diameter and fewer in number than in the first row.
5. The forming method according to claim 4, characterized in that: The gradient change is manifested in that the diameter of the reinforcing columns on both sides is 10% to 20% larger than that of the middle one; when arranged in two rows, the diameter of the second row of reinforcing columns is the same as that of the reinforcing columns on both sides of the first row.
6. The forming method according to claim 1, characterized in that: The explosive bonding material (4) is titanium-aluminum alloy powder, with a volume ratio of titanium to aluminum of 1:6 to 1:
4.
7. The forming method according to claim 1, characterized in that: The explosive bonding process involves covering the outer surface of the metal toothed ring edge (1) with a layer of plastic explosive with a detonation velocity of 2000-3000 m / s, and is carried out in a vacuum environment.
8. The forming method according to claim 1, characterized in that: The explosive bonding process is carried out at a temperature of 200-400℃ and a pressure of 200-500MPa, with an interfacial bonding strength ≥700MPa.
9. The forming method according to claim 1, characterized in that: The materials of the metal gear ring edging (1) include: tempered alloy steel, titanium alloy or metal-based composite material.
10. A near-all-composite material gear prepared according to any one of claims 1-9, characterized in that: It includes a resin-based composite gear matrix (3), a metal gear ring edging (1), a reinforcing column, and a connection interface formed by explosive bonding. The interface bonding strength between the metal gear ring edging (1) and the composite gear matrix (3) is ≥700MPa.
Citation Information
Patent Citations
Tooth reinforced MC nylon gear and preparation method thereof
CN113621232A
Composite material-steel double-material gear and preparation method
CN116428337A